HALAL BUSINESS TRAINING: STARTING AND DEVELOPING AN INNOVATIVE BUSINESS - syayyidah jannah (Journal of Islamic Economy and Community Engagement, 2021)
The halal industry has a great opportunity to develop in Indonesia. Muslim consumers who have a lot of demand for halal products in Indonesia are increasing. However, unfortunately, the halal products consumed are still imported. Therefore, to help encourage many businesses and MSMEs in Indonesia, many strategies are needed, one of which is training in business development. The training involves young entrepreneurs who are already successful in their business fields, as well as marketing experts. This training was attended by 100 participant that held by online (via zoom meeting). This training provides not only inspiration and experience but also business implementation strategies.